Natural resources used in the traditional medicine of the Marinaú community, Caxiuanã forest, Brazil - de Oliveira, Paula Maria Correa; Sousa, João Paulo Barreto; Albernaz, Lorena C.; Salmen Espindola, Laila; Coelho-Ferreira, Márlia (Frontiers in Pharmacology, 2024)
Background The diversity of Conservation Units in Brazil, ranging from Strict Protection areas like National Parks to Sustainable Use areas such as National Forests, supports the coexistence of human populations with extensive traditional knowledge of local natural resources. This traditional and local knowledge plays a crucial role in their subsistence and has significant potential to contribute to bioprospecting initiatives, as well as to enhance research and strategies for biological conservation. The São Sebastião de Marinaú community, situated within the Caxiuanã National Forest, offers valuable opportunities for ethnobiological studies. Methods The field study was carried out with 48 informants from the São Sebastião de Marinaú Community, Caxiuanã National Forest (CNF), Brazil, a Sustainable Use Conservation Unit. It involved participant observation, semi-structured interviews, and guided tours. Indices of Use Value (UV), Fidelity Level (FL), and Consensus Factor (ICF) indicated plant species with therapeutic potential. Results A total of 944 uses associated with 154 plants and 21 animals were reported. Statistical tests pointed out that factors such as gender and age are not determinants in the richness of known plants among the residents. The plants are distributed among 59 botanical families and 126 genera. They predominantly use species native to Brazil (69%), among which 47 are endemic to the Amazon. The medicines are prepared mainly by decoction of leaves and bark. According to UV, veronica (Dalbergia monetaria L.f.) was the most important. The animals used are all vertebrates, and paca (Cuniculus paca Linnaeus, 1766,) was the most cited. Bile and lard are the parts most used in the recipes. They mentioned 116 diseases, especially those of the digestive system. The ceruzeiro (Allantoma lineata (Mart. ex O.Berg) Miers) had a high consensus of local use, and no additional studies on this species exist. Conclusion This study underscores the vital role of traditional communities in sustainable conservation units, as their involvement is crucial for preserving plant and animal species essential to local traditional medicine. Such research also promotes the recognition of non-timber products as valuable raw materials with potential applications in the chemical and pharmaceutical industries. Additionally, mapping the occurrence and use of species in vulnerable conditions aids in developing effective conservation strategies for these resources.